A pilot study of elbow-shoulder coordination patterns during 3-point shots in players of different skill levels - Ahn, N.; Kipp, K. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to determine shoulder and elbow coordination between different skill levels in basketball players during 3-point shots. Digital video data were collected while five players performed 3-point shots. Video data were processed with Theia3D software, and shoulder and elbow joint angles were calculated in Visual3D. Vector coding analysis was used to calculate shoulder-elbow coupling angles. The mean coupling angles and frequency counts showed anti-phase coordination with elbow dominancy during ball release phase was consistent among all players. The results highlighted that high-skilled players may adopt more efficient shoulder and elbow coordination patterns to enhance their 3-point shots by taking relatively longer duration to adjust shoulder dominant in-phase coordination during shot preparation.